Governos estaduais no federalismo brasileiro: Capacidades e limitaç\~oes no cenário atual - Aristides Monteiro Neto (Instituto de Pesquisa Econômica Aplicada (IPEA), 2013)
– The main subject of this study is to propose an agenda to understand capabilities and limitations of state governments in Brazilian federalism. Governance capabilities, named here as economic-fiscal and political-institutional capabilities, are brought to the focus of the analysis. It is well known that our federalism has been recentralized in the past two decades and a small role is due to state governments. Otherwise the federal government in the president Lula administration has, after a decade (in the 1990's) of low levels of economic growth and repression on state budgets, boosted the national economy through expansion in social expenditures, public investment and public credit to the private sector. Very fruitful impacts were noted on state economies and finances but what it is not known is whether state governments had prepared themselves, in terms of strategic orientation and planning, to this new and positive scenario.
Keywords: H77; H11; R11; 330; intergovernmental relations; federalism; governance capabilities; regional and local development